DETERMINANTS OF DIVIDEND POLICY– EVIDENCE FROM POLISH LISTED ENERGY COMPANIES - Witkowska, Dorota; Kaźmierska-Jóźwiak, Bogna; Kompa, Krzysztof (Torun International Studies, 2024)
In this paper we study the dividend policy of the energy sector companies listed on the Warsaw Stock Exchange. We test the relationship between dividend values and the firm’s financial performance and other firm’s characteristics (firm’s size, the State Treasury's ownership and diversity in the sub-sectors) employing pooled regression models. The novelty of the study lies in the fact that to measure firms’ financial performance we use a multidimensional vector synthetic measure of their financial efficiency (VSMD). The empirical data were collected from EMIS and Notoria Service. The study results show that the determinants of the dividend value are the size of a company and the VSMD (the bigger company and the more efficient, the higher dividend paid).